2019
DOI: 10.1177/1359104519864129
|View full text |Cite
|
Sign up to set email alerts
|

Adapting treatment in an eating disorder program to meet the needs of patients with ARFID: Three case reports

Abstract: Avoidant/restrictive food intake disorder (ARFID) was introduced in the 5th edition of the Diagnostic and Statistical Manual of Mental Disorders. Three different subtypes of ARFID are described: individuals who seem disinterested in eating, those who avoid certain foods because of a sensitivity to specific characteristics of the food, and those who are concerned about an aversive experience associated with eating. There is currently no first-line treatment for ARFID. Three case studies are presented of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Furthermore, our results suggest that it is possible to treat ARFID successfully with only a therapist and physician, and without a large multidisciplinary team. Given that the majority of patients in our study received the family‐supported version of CBT‐AR, our findings are also consistent with recent case series (Lock et al, 2019b; Rienecke et al, 2020) and one pilot RCT (Lock et al, 2019a) that have reported positive effects of FBT for ARFID in children.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, our results suggest that it is possible to treat ARFID successfully with only a therapist and physician, and without a large multidisciplinary team. Given that the majority of patients in our study received the family‐supported version of CBT‐AR, our findings are also consistent with recent case series (Lock et al, 2019b; Rienecke et al, 2020) and one pilot RCT (Lock et al, 2019a) that have reported positive effects of FBT for ARFID in children.…”
Section: Discussionsupporting
confidence: 91%
“…Only three small randomized controlled trials have been published, and all have focused on young children ages 13 months to 12 years (Lock et al, 2019a; Sharp et al, 2016; Sharp et al, 2017). Published research on the treatment of older children and adolescents is limited to retrospective chart reviews (Bryson, Scipioni, Essayli, Mahoney, & Ornstein, 2018; Makhzoumi et al, 2019), case studies (Thomas, Brigham, Sally, Hazen, & Eddy, 2017), and case series (Dumont, Jansen, Kroes, de Haan, & Mulkens, 2019; Rienecke, Drayton, Richmond, & Mammel, 2020). A growing number of reports have highlighted the potential application of cognitive‐behavioral (Görmez, Kılıç, & Kırpınar, 2018; Steen & Wade, 2018; Zucker et al, 2019), family‐based (Eckhardt, Martell, Lowe, Le Grange, & Ehrenreich‐May, 2019; Lock et al, 2019; Rienecke et al, 2020; Spettigue, Norris, Santos, & Obeid, 2018), and parent‐management (Dahlsgaard & Bodie, 2019) approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, ARFID presents alongside a range of medical conditions. Several studies reporting on treatment-seeking individuals with ARFID clearly demonstrated nutritional deficiencies and related complications, such as dehydration and severe malnutrition due to a highly limited range of eaten foods [5][6][7] or a highly limited amount of oral food intake [8][9][10]. In a clinical sample of adolescents hospitalized for nutritional deficiencies, a significantly greater number of patients with ARFID were in need of enteral feeding compared with patients with anorexia nervosa [11], another highly restrictive eating disorder [1].…”
Section: Introductionmentioning
confidence: 99%
“…While there are currently no first-line recommendations for ARFID management, our multimodal interventional approach built upon that reported by other teams (Aloi et al, 2018; Chiarello et al, 2018; Dumont et al, 2019; Eckhardt et al, 2019; Lenz et al, 2018; Rienecke et al, 2020; Spettigue et al, 2018; ). CBT-based approaches have been reported to lead to increased food variety, reduced food avoidance, and/or improvement in psychosocial functioning among ARFID patients (Aloi et al, 2018; Bryant-Waugh, 2013; Chiarello et al, 2018; Dumont et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several ARFID case studies have been published highlighting the unique clinical features of this disorder (Table 1), with a limited number of studies describing patients with prolonged ARFID arising in early childhood or infancy and not associated with a specific triggering event (Aloi et al, 2018; Lock et al, 2019; Pitt & Middleman, 2018; Rienecke et al, 2020; Zucker et al, 2019). Evidence for therapeutic and pharmacological interventions in ARFID continues to be limited, with case studies describing use of family-based therapy (FBT), cognitive behavioural therapy (CBT) and/or antidepressant or atypical antipsychotic medications.…”
Section: Introductionmentioning
confidence: 99%